A spherical fountain prototype photoreactor operated under natural sunlight: Mechanism, toxicology assessment, and economics. (February 2023) - Muthukumar, Chandhini; Nagrikar, Swastik; Rodrigues, Derrick A.; Subramanian, Ramachandran; Palani, Sankar Ganesh; Changmai, Murchana; Prakash Kumar, B.G.
Abstract: Many investigations have reported the study of dispersed nanoparticle photocatalysts on a laboratory scale. Herein, we present a working spherical fountain prototype photoreactor spray-coated with galvanic sludge to prevent agglomeration and increase surface activity. The degradation process was performed under natural sunlight to make the process sustainable. This photocatalytic reactor exhibited an efficiency of 90.4 % during the photodegradation of 4-Nitrophenol at the optimal conditions of a pollutant concentration of 25 ppm with a photocatalyst loading of 5 g at a natural pH for an operating volume of 7 L with an addition of 0.7 mL of H2 O2 . Detailed specific surface area, pore volume, pore diameter, shape, and agglomeration were studied by BET and HRTEM. There was a significant change observed in the morphology and crystallinity of the recycled photocatalyst, which could be due to photo-corrosion, as shown in the FESEM and XRD analyses. Moreover, a detailed mechanism was elucidated to understand the fate of 4-Nitrophenol during photodegradation. Furthermore, a toxicology assessment was conducted for the pollutant before and after degradation using Escherichia coli, which showed a decrease in the toxicity. Lastly, an economic evaluation was carried out to deduce the cost of treating 1 m 3 of wastewater, which was determined to be USD 10.8/m 3 for this photoreactor model. Graphical abstract: Unlabelled Image Highlights: A spherical fountain prototype photoreactor operated in natural sunlight was reported. The galvanic sludge-coated photoreactor imparted an efficiency of 90.4 % in degrading 4-Nitrophenol. A plausible degradation pathway for 4-Nitrophenol was proposed. The total treatment cost for photodegradation was determined to be USD 10.8/m 3 .